"They Will Have to Protect Themselves": African American Resistance to Racialized Violence in the Southern United States - Whitwell, Sarah (My University, 2020)
Black men and women were the victims of verbal abuse, neglect, intimidation, rape, physical assault, lynching, and other manifestations of violence in both the late antebellum and postemancipation South. This dissertation reconstructs how the newly freed black population experienced racialized violence during the transition from slavery to freedom and in the decades immediately following emancipation. By analyzing primary source collections that chronicle the transitional period between slavery and freedom, it is possible to frame resistance to racialized violence as part of a continuum. The struggle to combat racialized violence, I argue, was conditioned by the experiences of black men and women during slavery. This dissertation, then, highlights the continuities that existed in a period of apparent discontinuity. To reconstruct the experiences of black men and women, this dissertation also reconceptualizes how we think about violence and resistance. There is a tendency among scholars who study racialized violence to equate violence with the use of physical force. This dissertation, however, defines violence as the use of physical force or power, threatened or actual, that either results in or has a high likelihood of resulting in injury, death, psychological harm, maldevelopment, or deprivation. By adopting a definition of violence that is broader than those used in most existing studies of racialized violence, it becomes possible to understand the long-term, psychological, and developmental impact of racialized violence on black men and women. Resistance, similarly, must be understood in broader terms to include acts that are not explicitly recognized as resistance by those involved, but that informed observers might perceivably recognize as thwarting an attempt at subjugation. The reality is that overt resistance was dangerous for African Americans, and so many turned towards clandestine methods of resistance to voice their opposition.
Keywords: African American History; American History; Digital History